The Effect of Ecoprint Activities on the Fine Motor Development of Children Aged 5-6 Years - Suroto, Muslimah; Febriyanti; Lidia Oktamarina (UNIB Press, 2026)
The fine motor development of early childhood is often not optimal due to a lack of variety in learning media that can stimulate hand-eye coordination and finger skills. Based on initial observations at RA Al-Hidayah Palembang, 17 children aged 5–6 years were found to have below-standard fine motor skills, especially in writing, cutting, and pasting activities. This study aims to analyze the effect of ecoprinting activities as a natural material-based learning medium on children's fine motor development. The research method used a quantitative approach with a One Group Pretest–Posttest design. The research sample consisted of 17 children selected through purposive sampling. Data were collected through observation, tests, and documentation, then analyzed using a paired sample t-test. The results showed a significant increase between the pretest and posttest scores, as evidenced by a t-value of −9.581, which is greater than the t-table value of 2.120, and a significance value of p < 0.001. These findings indicate that ecoprinting activities are effective in improving children's fine motor skills, especially in terms of accuracy, finger flexibility, grip strength, and visual-motor coordination. Therefore, ecoprint can be used as an alternative learning medium that is enjoyable, environmentally friendly, and capable of stimulating optimal fine motor skill development.